If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -10) = 2x + -10 Reorder the terms: 3(-10 + x) = 2x + -10 (-10 * 3 + x * 3) = 2x + -10 (-30 + 3x) = 2x + -10 Reorder the terms: -30 + 3x = -10 + 2x Solving -30 + 3x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -30 + 3x + -2x = -10 + 2x + -2x Combine like terms: 3x + -2x = 1x -30 + 1x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 -30 + 1x = -10 + 0 -30 + 1x = -10 Add '30' to each side of the equation. -30 + 30 + 1x = -10 + 30 Combine like terms: -30 + 30 = 0 0 + 1x = -10 + 30 1x = -10 + 30 Combine like terms: -10 + 30 = 20 1x = 20 Divide each side by '1'. x = 20 Simplifying x = 20
| 13-4(5x+1)=3(7-5x)-9 | | 10k+4K=-14 | | 28-4a=6(2a-2)-24 | | 2(x+8)=2(2x) | | 7w+2w(w+5)=5 | | 7m-5=58-2m | | 20+2y-6y-4x=0 | | 42-p=18 | | 5(2q-1)+15=10q+50 | | 4-p=17 | | 3.75=0.625K | | 20=28+n | | x+2x+3+4=5x+6x+7+8 | | 2n+4=m | | 4r+5=11 | | 13+29=3a-14+2a | | y=2x+3y+1.5 | | 10+N-15=4 | | 3x+9+4x+1=7x+9 | | 3x+9+4x+x=0x+0 | | -12=-8+a | | 5(3x-2)-x=12x+6 | | v/5-16=10 | | 7x+4x-8x-5=7 | | 3x+9+4x+1=4x+6 | | 4(-8-x+5)=-32x-26 | | 8(3)^(x/2) | | (4x-13)(3x-2)=0 | | -(-a)-(-3)=-4 | | 5+4*3=x | | 9x+13x=88 | | 5+4*3= |